Peningkatan Kualitas Tidur Anak Hospitalisasi Yang Megalami Gangguan Pola Tidur Menggunakan Teknik Sleep Hygiene - JUPRI KARTONO; Dewi Damayanti; Mar’atun Nufus Sholihah (Madago Nursing Journal, 2022)
Hospitalization is a condition that destroys children living in a hospital, undergoing therapy and treatment for a reason that is planned or an emergency. Hospitalization has been shown to cause restless sleep disorders, the client's inability to get a comfortable position and pain is the most common cause of sleep rest disorder. Sleep Hygiene Therapy is a term used to describe good sleep habits or patterns. Sleep Hygiene as a non-pharmacological therapy for sleep disorders, promotes the formation of sleep routines, good and quality sleep patterns. This study aims to determine and analyze the quality of sleep after applying sleep hygiene to school-age children undergoing hospitalization. The method in this study is applied research involving 2 subjects. The results showed that after being given sleep hygiene therapy in children who experienced sleep patterns during hospitalization in both respondents there was a change in sleep quality from severe sleep pattern disorders to mild. The conclusion of this study is that there is an effect of sleep hygiene intervention on the problem of sleep pattern disorders in school-age children undergoing hospitalization.